Laboratory performance and fracture resistance of CAD/CAM implant-supported tooth-coloured anterior FDPs. (May 2020) - Zacher, Julian; Bauer, Robert; Strasser, Thomas; Rosentritt, Martin
Abstract: Objectives: This study investigated the in-vitro performance and fracture force of anterior implant-supported tooth-coloured fixed dental prosthesis (FDPs). Different material types with varying flexural strength and modulus of elasticity were compared with screw-retained or bonded application. Materials and methods: Identical anterior FDPs (tooth 11–13; n = 80) from materials (flexural strength 240−1150 MPa, modulus 7.6−210 GPa; 1x lithiumdisilicate ceramic, 2x zirconia (4Y-TZP, 5Y-FSZ), 3x resin-based composites (with different flexural strength and modulus)) were milled. FDPs were grouped into chairside (bonded) and labside (screw-retained) procedure. To simulate a 5-year clinical application, thermal cycling with mechanical loading (TCML) was accomplished. TCML-performance and fracture force were evaluated and failure patterns were analysed. Data were statistically investigated (Kolmogorov-Smirnov-test, one-way-ANOVA; post-hoc-Bonferroni, α = 0.05). Results: TCML did not lead to any cracks, fractures or chipping on all tested FDPs. Fracture values varied between 1208.9 ± 354.6 N (experimental resin-based composite) and 2094.3 ± 293.4 N (4Y-TZP) for FDPs without screw channel. With screw channel the results ranged between 1297.9 ± 268.3 N (5Y-FSZ) and 2129.3 ± 321.7 N (4Y-TZP). The influence of the screw channel was not significant for all materials (p ≥ 0.218). Modulus of elasticity and flexural strength had influence on the fracture force only in the individual material groups. Fractures at the connector were predominant for ceramic and zirconia. Resin-based composites primarily showed radial fractures in abutment region or mixed failure types. FDPs with/without screw-channel showed comparable types of failure. Conclusions: TCML did not lead to drop-outs or failures for all FDPs. Individual materials showed no different in-vitro performance, but varying fracture force after TCML. Independent from material, screw channels did not weaken the FDPs. All tested systems showed sufficient properties for an anterior implant application.